Competency based compensation system - S Monica; R Sarvamangala (Journal of Management and Science, 2022)
In Today’s competitive Business environment, employees play’s a major role, human resource management helps in bringing people and organization together to achieve their goals. Earlier organization was completely depended upon the financial aspects,but in present Business scenarios, the success of the organization depends upon the human resource, hence the organization should hire the competent employees. Basically this study is conceptual based system on competency based compensation system. The paper makes an attempt to tell how the competencies in the workplace help in compensating the employees. Employees should be compensated based on their performance and competencies “Compensated based on their performance is better than just compensating without considering their job”. Compensating the employees by their performance motivate the employees much more to work towards the organization goal. Employees will get more attracted towards work and perform better to get compensated wherein it benefits the organization itself.